À la lisière de l’« autre monde ». Le Pérou dans la Relatione breve de Diego de Torres Bollo (1603) - Pierno, Franco (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2011)
In 1603, Diego de Torres Bollo (1550–1638), Jesuit procurator of the province of Peru, published in Rome his Relatione Breve, one of the first printed accounts of early Jesuit missionary activities in South America. The work was an instant success: in 1604 a second Italian edition was published in Venice, as well as translations into Latin (Antwerp) and French (Paris). The Relatione was typical of many Jesuit accounts of the period, that is, it consisted of a skillfully arranged montage of letters from the missions, written for the express purpose of attracting new vocations to missionary work in South America. To the detriment of this editorial success, with the exception of the major bibliographical repertories, de Torres Bollo’s text is rarely used and seldom cited by historians, and is even paradoxically absent in historical undertaking such as Rubén Vargas Ugarte’s Historia de la Compañía de Jesús en el Perú; furthermore, there is no modern edition, not even a diplomatic transcription, in the important Monumenta Peruana. With this contribution, I intend not only to inform those who read a little-known work, but also to demonstrate how it constitutes a decisive moment in the genesis of the “relation” genre in the first decades of written Jesuit communication.